Design of a New Geoid-Based Vertical Datum for Costa Rica - Pimenova, Olga (2023)
Pimenova, O. (2023). Design of a New Geoid-Based Vertical Datum for Costa Rica. [Tesis de Doctorado]. University of New South Wales, Australia, Sydney.